Reorienting programme budgeting and marginal analysis (PBMA) towards disinvestment - Mortimer Duncan (BMC, 2010)
Abstract Background Remarkable progress has been made over the past 40 years in developing rational, evidence-based mechanisms for the allocation of health resources. Much of this progress has centred on mechanisms for commissioning new medical devices and pharmaceuticals. The attention of fund-managers and policy-makers is only now turning towards development of mechanisms for decommissioning, disinvesting or redeploying resources from currently funded interventions. While Programme Budgeting and Marginal Analysis would seem well-suited to this purpose, past applications include both successes and failures in achieving disinvestment and resource release. Discussion Drawing on recent successes/failures in achieving disinvestment and resource release via PBMA, this paper identifies four barriers/enablers to disinvestment via PBMA: (i) specification of the budget constraint, (ii) scope of the programme budget, (iii) composition and role of the advisory group, and (iv) incentives for/against contributing to a 'shift list' of options for disinvestment and resource release. A number of modifications to the PBMA process are then proposed with the aim of reorienting PBMA towards disinvestment. Summary The reoriented model is differentiated by four features: (i) hard budget constraint with budgetary pressure; (ii) programme budgets with broad scope but specific investment proposals linked to disinvestment proposals with similar input requirements; (iii) advisory/working groups that include equal representation of sectional interests plus additional members with responsibility for advocating in favour of disinvestment, (iv) 'shift lists' populated and developed prior to 'wish lists' and investment proposals linked to disinvestment proposals within a relatively narrow budget area. While the argument and evidence presented here suggest that the reoriented model will facilitate disinvestment and resource release, this remains an empirical question. Likewise, further research will be required to determine whether or not the re-oriented model sacrifices feasibility and acceptability to obtain its hypothesised greater emphasis on disinvestment.